The Impact of Health Corporate Socıal Responsıbılıty (CSR) Actıvıtıes on Brand Attıtude and Customers’ Loyalty in Two Bıg Cıtıes of Indonesıa - Elevita Yuliati; Tengku Ezni Balqiah; Nurdin Sobari; Rifelly Dewi Astuti (Department of Management, Faculty of Economics and Business, Brawijaya University, 2017)
This paper examines whether health CSR activities – CSR activities concerning health and well being of mothers and children – conducted by companies will promote perceived quality of life, consumers’ brand attitude, and customers’ loyalty, with subjective well-being serves as moderating variable. The research will use both exploratory and conclusive researches. Surveys were conducted in two cities in Indonesia, Makassar and Surabaya. The subjects of this research are customers of three companies operating in Indonesia, namely Pertamina, Danone-Aqua, and Frisian Flag, and also people in the communities exposed to the companies’ health CSR activities. These companies are chosen due to their continuous health CSR activities during the past years. The total number of respondents are 240 respondents, consists of 90 customers and 30 community members from each city. The data were analyzed using multiple regressions to test 9 research hypotheses. The result shows that different motivations were generated from different CSR activities by all three brands, and had different path to influence social and business performance.